The Effect of Service Quality on Gojek Online Customer Satisfaction - Muhammad Rizqi; Afriapollo Syafarudin (Ilomata International Journal of Tax and Accounting, 2021)
Good service quality can be a competitive advantage for service companies. Quality of service is also the key to success. Whether or not the quality of service for goods or services depends on the ability of producers to consistently meet consumer expectations. Service quality is said to be satisfactory if the service felt is the same or exceeds the expected service quality. Services like this are perceived as quality and satisfying services. These consumer expectations are reflected in good service, warm hospitality, courtesy, punctuality, and speed which are important values ​​expected by consumers. Satisfied consumers will indirectly encourage word-of-mouth recommendations, and can even improve the company's image in the eyes of consumers. Therefore, service quality must be the main focus of company attention because it can create customer satisfaction. This study aims at the influence of service quality on customer satisfaction. Respondents of this study used 100 research samples on Gojek brothers, the tools used in this study were using the PLS (Partial Least Square) analysis method. The results of the analysis of this study are the effect of service quality on customer satisfaction